Self-assembly of carbohydrate-based small amphiphiles and their applications in pathogen inhibition and drug delivery: a review. Issue 11 (14th May 2021) - Mittal, Ayushi; Krishna; Aarti; Prasad, Suchita; Mishra, Prashant Kumar; Sharma, Sunil K.; Parshad, Badri
Abstract : Carbohydrate-based amphiphiles: self-assembled nanostructures of defined size and shape for various biomedical applications. Abstract : Carbohydrates are naturally occurring compounds that are biocompatible, biodegradable and offer good opportunities for chemical modifications. Also, they hold significant importance in numerous biological processes including immune response, growth regulation, cell signalling, adhesion and fertilization. Due to these characteristics carbohydrates have been successfully incorporated in amphiphilic architectures and are being used for biomedical applications such as drug delivery, gene therapy, diagnostic imaging and photosensitizer delivery. Amphiphiles self-assemble in an aqueous medium, producing myriad nanostructures with unique morphologies and properties. Herein, we review the recent developments in the area of carbohydrate-based small non-ionic amphiphiles and their self-assembly in an aqueous medium to produce various nanostructures at the molecular level. Special attention has been paid to highlight their supramolecular self-assembly behaviour and on applications of the formed self-assembled nanostructures in pathogen inhibition and drug delivery.